The quality of reporting and publication status of vaccines trials presented at veterinary conferences from 1988 to 2003 - Brace, Samantha; Taylor, Dan; O’Connor, Annette M. (Vaccine, 2010)
Conference proceedings, although an importance source to learn about new interventions, are brief and not subject to external evaluation prior to publication. Studies in human medicine suggest that trial results from conference proceedings may be poorly reported. The primary objective of this study was to evaluate characteristics of veterinary vaccine studies published in conference proceedings. 154 cattle or swine vaccine trials presented at veterinary practitioner conferences held in the United States from 1988 to 2003 were the test base to evaluate the following: abstract-to-publication ratio, positive-outcome ratios, differences between proceeding and subsequent journal articles, and compliance with the CONSORT Statement extension for abstracts. The abstract-to-publication ratio was 5/89 for swine trials and 6/65 for cattle trials. The positive-outcome ratio for swine conference proceeding and journal articles was 57/89 and 4/5 respectively. The positive-outcome ratio for bovine conference proceeding and journal articles was 34/65 and 4/6 respectively. No major differences were found between conference proceedings and matching journal articles. Fewer than 10% of conference proceedings included: identification of the trials as randomized in the title, study design as field or challenge; the primary outcome; trial status; results for primary outcome; information about harms and funding source (2/89). When conference proceedings are subsequently published in journals; there is no significant difference in the data, however subsequent publication is uncommon. For many conference proceedings it would be difficult to assess the internal and external validity of the trial based on the information reported.